Penyelesaian Kasus Kecelakaan Lalulintas Berat dengan Pendekatan Restoratif - Tegar Ariwibawa; Neni Vesna Madjid (UNES Law Review, 2023)
Article 310 paragraph (3) of Law Number 22 of 2009 concerning Road Traffic and Transportation regulates the types of serious traffic accidents. This research is an empiricaljuridical research. Settlement of heavy class traffic accidents with a restorative justice approach as an alternative model for solving traffic violations at the South Pesisir Resort Police is carried out by forgiving each other by both parties, then the crashing party undertakes to provide compensation to the victim, and helps with medical and repair costs. victim's vehicle. The victim is willing to do restorative justice because an accident is a disaster for road users. No one wants this problem so that the settlement is considered fair. The parties made peace in writing which was known to the Wali Nagari where the victim was domiciled, so the letter was handed over to the traffic accident investigator that both parties in the traffic accident case wanted to resolve it amicably. Obstacles in solving heavy traffic accidents using the Restorative Justice approach at the Pesisir Selatan Police are first, the settlement of traffic crimes through restorative justice for heavy class accidents does not yet have a legal umbrella; secondly, the amount of compensation demanded by victims is often too large to give the impression of being used as a means of seeking profit; third, the limited economic capacity of the perpetrators of traffic crimes (severe class accidents); fourth, the involvement of certain parties that are not directly related to the accident often becomes an obstacle to reaching an agreement between the perpetrator and the victim.